Prospects of low carbon development for Pakistan’s energy and power sector in the post Covid scenario - Ubaid ur Rehman Zia; Hina Aslam; Muhammad Zulfiqar; Sibghat Ullah (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
In the backdrop of COVID19 recovery, Pakistan is still struggling to cope with the economic challenges and disruptions caused in the energy supply chain. On one hand where COVID has brought serious socio-economic costs and prolonged delays, it has also provided opportunity for developing countries such as Pakistan to “build-forward-better” their economies in a more sustainable and climate friendly manner. This study particularly highlights the impact of COVID on energy supply and demand sectors of Pakistan, its near- and long-term impacts, and what policy interventions can be adopted to put Pakistan on-track to achieve its Nationally Determined Contributions (NDCs). The economic focus in on “Green Recovery” and what key interventions will foster a rapid transition towards decarbonization in Pakistan. Low Emission Analysis Platform (LEAP) model is used to provide energy sector outlook (2020-2040) of Pakistan under different scenario i.e., Pre COVID growth, Business-as-Usual, Slow Recovery, and Green Recovery from COVID. The results obtained from the model depicts that following a green recovery scenario, Pakistan can reduce around 10 Mtoe (9%) of its total energy use, 53 TWh of electricity, 19 Mt of emissions from demand sectors, and 11 Mt of emissions from the power sector by 2030. For total levelized cost of the power sector, the green recovery scenario represents a generation cost of 13 billion by 2030 which further highlights that energy efficiency could lead to cost savings of approximately 3 billion each year by 2030. Green recovery is however still a daunting task as it would require economic stimulus of 8 billion only to recover to its pre COVID scenario and total investments of 120 billion by 2030.